Effectiveness of Cocoa Pod Husk Extract Toothpaste against Staphylococcus aureus In Vitro - Sefblianda, Thisa; Syahputra, Armia; Octavia Nasution, Rini; Amalia, Martina (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This study investigates the antibacterial activity of toothpaste formulated with Theobroma cacao L. pod husk extract against Staphylococcus aureus ATCC®29213. The extract was incorporated into toothpaste formulations at concentrations of 2.5%, 5%, and 10%. The antibacterial activity was evaluated using the well diffusion method, and inhibition zones were measured after a 24-hour incubation period at 37°C. The results showed that all concentrations of the toothpaste exhibited significant antibacterial effects, with the 10% concentration demonstrating the highest efficacy. Phytochemical screening revealed the presence of bioactive compounds such as flavonoids, alkaloids, saponins, and terpenoids, which are known for their antimicrobial properties. The 10% concentration of the extract showed the largest inhibition zone, reaching 19.3 mm, significantly higher than the 2.5% and 5% concentrations, which yielded zones of 13.4 mm and 15.9 mm, respectively. While the positive control (Siwak-F) demonstrated the highest inhibition zone (20.9 mm), the cocoa pod husk extract at 10% concentration showed comparable efficacy. Physical evaluations of the toothpaste formulations indicated good stability, with acceptable levels of pH, spreadability, and viscosity. These findings suggest that Theobroma cacao pod husk extract has potential as a natural antibacterial agent in toothpaste formulations, offering an alternative to synthetic chemical agents.